Cardiometabolic factors explaining the association between physical activity and quality of life: U.S. National Health and Nutrition Examination Survey - Frederick H. Huang; Jung-Hua Liu; I-Chan Huang (Journal of Exercise Science & Fitness, 2022)
Background/Objective: To test the Clustered Cardiometabolic Risk (CCMR) factor explaining the relationship between physical activity and physical quality of life (QOL). Methods: Using the U.S. National Health and Nutrition Examination Survey 2003–2006, 2,445 adults completed the CDC Healthy Days Questionnaire for measuring QOL, wore the accelerometer for assessing physical activity pattern (PAP), and completed triglyceride, glucose, serum insulin, waist circumference, blood pressure, and HDL-cholesterol tests from which the CCMR factor was created. Physical QOL was classified as poor (≥14 days with poor physical health within past 30 days) vs. good (<14 days). We classified PAP by moderate-to-vigorous physical activity (MVPA), light-intensity physical activity (LIPA), and sedentary behavior (SB). We defined MVPA, LIPA, and SB as ≥2020 counts/minute, 100–2019 counts/minute, and ≤99 counts/minute, respectively. We further classified PAP status as unhealthy (MVPA <150 min/week & SB>LIPA) or healthy (MVPA <150 min/week & SB<LIPA, or MVPA ≥150 min/week regardless of SB>LIPA or SB<LIPA). Logistic regressions analyzed the association between unhealthy PAP and poor physical QOL, adjusting for the CCMR factor, age, sex, education, and smoking behavior. Results: Compared with having healthy PAP, individuals having unhealthy PAP had an elevated risk of poor physical QOL (OR = 1.96; 95% CI = 1.42–2.72). However, this association was explained by higher levels of the CCMR factor (OR = 1.46; 95% CI = 1.07–1.99) through poorer serum insulin (OR = 1.35; 95% CI = 1.04–1.75) and waist circumference (OR = 1.23; 95% CI = 1.02–1.50). Conclusion: The CCMR factor (typically insulin and waist circumference) explained the association between unhealthy physical activity and poor physical QOL.